Identifikasi Pemahaman Konsep Siswa pada Materi Titrasi Asam Basa - Rumape, Opir; Adjami, Eka Nur Fadliya; Pikoli, Masrid; Sihaloho, Mangara; Iyabu, Hendri; Abas, Ramona Nintias R. (Jambura Journal of Educational Chemistry, 2024)
This research was conducted to identify the level of students' conceptual understanding in acid-base titration material for class XI IPA MAN I Gorontalo City. This research is descriptive research, the instrument used in this research is a two-tier multiple choice diagnostic test consisting of 10 item questions. This instrument has been tested for validity with validation results obtained at 100%. The research respondents were 118 students of class XI IPA at MAN I Gorontalo City. Data collection was obtained by means of observation, giving tests and documentation. The results showed that students' understanding of the concept of acid-base titration material in the understanding category was 80%, in the category of misconceptions was 13%, in the category of guessing was 2%, and in the category of not understanding the concept was 5%. So it can be concluded that students' understanding of acid-base titration material tends to understand the concept.